SIMULATION OF WAVE SUPERPOSITION WITH VISUAL BASIC 6.0 - NURIDHA (NIM 20207047), MUHAMMAD
Wave Simulation by means of Visual Basic 6.0 is aimed to ease understanding of superposition of wave. We developed visualization for mechanic wave superposition and interference of wave on the narrow slit. By these simulations, the explanation of mechanic wave superposition and wave interference become easier, and more interactive. Simulation of wave superposition shows the mixing of two mechanic wave and their resultant. Beside that, simulation of wave interference on narrow slit can show intensity as a function of phase to the interference of N slits.